1993
DOI: 10.1103/physrevlett.71.1230
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of conductance fluctuations in quantum dots

Abstract: We present a complete analytical theory of conductance fluctuations in quantum dots in the regime of chaotic dynamics. Using the supersymmetry method we calculate for the first time exactly the conductance distribution function for a system of noninteracting electrons. Knowledge of this quantity enables us to obtain information about statistical properties of wave functions of a closed dot. The far tail of the distribution function describes fluctuations of resonance conductance in the Coulomb blockade regime.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
140
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 12 publications
9
140
2
Order By: Relevance
“…This alternative argument [27] immediately yields the functional form (27). When the closed dot is defined by the Dirichlet boundary conditions, the wave function in the narrow strip S near the "edge" can be represented asψ = zϕ (y) (28) where y is the coordinate along the boundary of the dot and z is in the direction of the normal. In this limit, the correlation function is…”
Section: Peak Heights Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…This alternative argument [27] immediately yields the functional form (27). When the closed dot is defined by the Dirichlet boundary conditions, the wave function in the narrow strip S near the "edge" can be represented asψ = zϕ (y) (28) where y is the coordinate along the boundary of the dot and z is in the direction of the normal. In this limit, the correlation function is…”
Section: Peak Heights Distributionmentioning
confidence: 99%
“…By using the correlation function of a random superposition of plane waves, the probability distributions of level-widths and conductance peaks in the case of multi-mode leads to the quantum dot were found [11,26]. A distribution similar to this ansatz was derived microscopically for disordered systems, a specific kind of chaotic system, using the nonlinear sigma model [28][29][30][31]. The next step was to constrain the correlation function by the short-time classical dynamics.…”
Section: Wave Functions In the Dot: The Statistical Descriptionmentioning
confidence: 99%
“…The theory unifies and extends known results. [2][3][4] The characteristic β-dependence of the distribution function that was found for ideal leads [Eq. (1)] is strongly suppressed for transmission probabilities T larger than Γ 2 . A closely related phenomenon is the nontrivial Γ-dependence of the conductance fluctuations for the three symmetry classes.…”
mentioning
confidence: 99%
“…Recently, it was found that a "quantum dot" has a qualitatively different conductance distribution. [2][3][4] A quantum dot is a small confined region, having a large level spacing compared to the thermal energy, which is weakly coupled by point contacts to two electron reservoirs. The classical motion within the dot is assumed to be ballistic and chaotic.…”
mentioning
confidence: 99%
“…To illustrate how it works, we are going then to apply it to the case of a flat microwave cavity to which a thin antenna is attached. We compute the resonance spacing distribution in this system and show that it reproduces experimental data -within certain range of energies but without introducing any free parameters.Many recent studies involve an analysis, both theoretical and experimental, of spectral and transport properties of systems with a complicated geometry: let us recall various microwave resonators [1,2,3,4,5] or conductance fluctuations in quantum dots -see [6,7,8,9] and references therein. …”
mentioning
confidence: 99%